A novel MIP mutation in a Chinese family with congenital cataract. (4th July 2018) - Yuan, Chao; Han, Tiantian; Su, Pan; Liu, Min; Zhou, Xiaopei; Zhang, Dazhi; Jia, Weimin; Wang, Ali; Yue, Min; Xiang, Zibing; Chen, Liming; Zhang, Xianqin
ABSTRACT: Purpose : To identify the disease-causing gene of a four-generation Chinese family with congenital cataract. Methods : To screen the disease-causing gene of the family, six disease genes of congenital cataract are screened by direct DNA sequencing, the cDNA of wild-type (WT) MIP gene, and P191R mutant MIP gene (MT) were constructed into pEGFP-C1 vector and pGH19 vector. The recombinant plasmids of pEGFP-C1, WT, and mutant MIP were transfected into Hela cell to check the localization and HEK293T cells to detect expression level of protein. The cRNA of WT and MT MIP gene were injected into Xenopus oocytes to measure the swelling rate. Results : A novel missense mutation c.572C>G（p.P191R）at exon 3 of the MIP gene was identified and co-segregated with disease in the Chinese family. The same amount of pEGFP-WT MIP and pEGFP- P191R MIP plasmids were transfected in Hela cells. Confocal microscopy imaging showed that WT MIP protein predominantly localized on the plasma membrane, the mutant protein was rich in the cytoplasm in Hela cells. Western blot results show that the expression level of P191R mutant MIP was significantly lower than WT MIP incell membrane enriched lysates in HEK293T cells. Xenopus oocytes swelling assay showed that the P191R mutation reduces the swelling rate of Xenopus oocytes. Conclusions : The novel missense mutation c.572C>G（p.P191R）at exon 3 of the MIP gene was identified in a Chinese family of congenital cataract. The mutation affects the traffic of MIP protein in the cells and reduces the expression level of MIP protein in the cell membrane. The mutation of MIP gene reduces the swelling ratio of Xenopus oocytes.